Management of Meloidogyne incognita on tobacco through Glomus aggregatum and oil cakes - Serfoji, P (International Journal of Pharmaceutical & Biological Archive, 2013)
Management of Meloidogyne incognita on tobacco through Glomus aggregatum and oil cakes